2002
DOI: 10.2320/matertrans.43.2408
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grain Boundary Sliding in Microstructural Evolution during Superplastic Deformation of a 7055 Aluminum Alloy

Abstract: The microstructure evolution in a 7055 aluminum alloy subjected to thermomechanical processing (TMP) was studied at 450 • C anḋ ε = 1.7 × 10 −3 s −1 at which the material exhibits superplastic behavior with a total elongation of 720% and the coefficient m = 0.58. Partially recrystallized initial structure of the as-processed 7055 Al consisted of bands of recrystallized grains with a mean size of 11 µm alternating with bands of recovered subgrains with a mean size of 2 µm. The true stress-true strain curve exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…It is shown that the superplastic behavior of aluminum alloys in the unrecrystallized structure could be attributed to grain boundary sliding along high-angle grain boundaries. This grain boundary sliding along separate high-angle grain boundaries induces rotation in subgrains and facilitates transformation of low-angle grain boundaries to high-angle grain boundaries [25]. Therefore, uniform subgrain structure seems to provide enhanced grain boundary sliding and further transformation of low-angle grain boundaries to high-angle grain boundaries which leads to achieving higher elongations than banded subgrain structure.…”
Section: Resultsmentioning
confidence: 97%
“…It is shown that the superplastic behavior of aluminum alloys in the unrecrystallized structure could be attributed to grain boundary sliding along high-angle grain boundaries. This grain boundary sliding along separate high-angle grain boundaries induces rotation in subgrains and facilitates transformation of low-angle grain boundaries to high-angle grain boundaries [25]. Therefore, uniform subgrain structure seems to provide enhanced grain boundary sliding and further transformation of low-angle grain boundaries to high-angle grain boundaries which leads to achieving higher elongations than banded subgrain structure.…”
Section: Resultsmentioning
confidence: 97%
“…This is related to the fact that the HABs can efficiently absorb the dynamically generated dislocations [30,31]. The simulation of microstructural evolution during CDRX has denoted that at such large strains the dynamic recovery alone is unable to justify the restoration of microstructure [13] and that misorientations are mainly increased by grain boundary sliding [32]. The latter analogy may be held for SPD of magnesium alloys to very large strain at such a high temperatures (330 C).…”
Section: Resultsmentioning
confidence: 96%
“…When the feed rate is 0. 5 mm, 1 mm and 1.5 mm, the minimum grain size is 0.75 µm, 0.83 µm and 0.67 µm at low temperature, respectively; and the minimum grain size is 0.54 µm, 0.75 µm and 0.55 µm at the high temperature environment, respectively [11]. At the same feed rate, the dislocation density at low temperature is higher than that of high temperature, and the grain size at low temperature is higher than that of high temperature too.…”
Section: Resultsmentioning
confidence: 99%